Analisis Kinerja Ruas Jalan Jendral Ahmad Yani Kota Kendari (Studi Kasus : Studi Kasus Depan SPBU Bongoeya) - Irwan Lakawa; Catrin Sudardjat; Fahram Haerozi (Sultra Civil Engineering Journal (SCiEJ), 2026)
Ahmad Yani Street in Kendari City is one of the main road segments with high traffic activity, especially during peak hours. This study aims to analyze the road performance by examining traffic volume, side friction, speed, degree of saturation, and level of service (LOS). Data were collected through field surveys for three days during morning, afternoon, and evening peak hours. The observation segment spans 200 meters, from the front of SMP Negeri 4 Kendari to the front of Ittifaqul Jama’ah Mosque. The analysis results indicate that traffic volume is higher on Segment B, influenced by the presence of a gas station and school, while Segment A experiences smoother flow due to the presence of only a mosque. The highest side friction is also found on Segment B. The free-flow speed (FFS) is recorded at 49 km/h on Segment A and 47 km/h on Segment B. The actual travel speed (VT) is 35 km/h for Segment A and 28 km/h for Segment B. The degree of saturation is 0.70 on Segment A and 0.80 on Segment B. Based on these values, the level of service for Segment A falls into category C, while Segment B is in category D. These findings indicate that Segment B's performance requires further attention to improve traffic flow.